On lingering and literature - Schweizer, Harold, 1950- (Abingdon, Oxdon ; New York, NY : Routledge, 2021)
Lingering and its decried equivalents, such as dawdling, idling, loafing, or lolling about, are both shunned and coveted in our culture where time is money and where there is never quite enough of either. Is lingering lazy? Is it childish? Boring? Do poets linger? (Is that why poetry is boring?) Is it therapeutic? Should we linger more? Less? What happens when we linger? Harold Schweizer here examines an experience of time that, though common, usually passes unnoticed. Drawing on a wide range of philosophic and literary texts and examples, On Lingering and Literature exemplifies in its style and accessible argumentation the new genre of post-criticism, and aims to reward anyone interested in slow reading, daydreaming, or resisting our culture of speed and consumption.
OCLC-licensed vendor bibliographic record.
Keywords: Lingering in literature; Time perception in literature; LITERARY CRITICISM / General